PENGEMBANGAN INTEGRATED SCIENCE ASSESMENT BERBASIS PISA UNTUK PESERTA DIDIK KELAS VII SMP - Indri Nurwahidah; Yeni Widiyawati; Dwi Septiana Sari (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2019)
This study aims to develop an integrated science assessment based on PISA in Class VII IPA material. This type of research is Borg & Gall's research and development. The assessment was developed in the form of reasoned multiple choice questions in odd grade VII grade science material. The questions of integrated science assessment were developed based on themes that are closely related to the daily lives of students. Based on the results of the validation of experts and junior high school science teachers for the components of content, presentation, and language, it can be concluded that the instruments developed were valid with very good categories. Thus, integrated science assessment based on PISA is appropriate for use in learning.